Vendor pushes a sled filled with frozen fish to his stall in the open-air meat and fish market in Yakutsk, Russia - Campbell, Sandy (2014)
The open-air meat and fish market in Yakutsk, Russia offers frozen fish, meats, berries, mushrooms and vegetables, as well as some clothing. Most of the fish come from lakes and rivers in the Sahka Republic, while some are imported. The meats include horse, reindeer, beef and pork. The meat is government-inspected and offered as quarters and cuts. Offal is also available. By the end of November the daytime temperature is in the range of -20C to -30C, so the meat and fish stay frozen.